Sequence Variants and the Risk of Head and Neck Cancer: Pooled Analysis in the INHANCE Consortium - Chuang, Shu-Chun; Agudo, Antonio; Ahrens, Wolfgang; Anantharaman, Devasena; Benhamou, Simone; Boccia, Stefania; Chen, Chu; Conway, David; Fabianova, Eleonora; Hayes, Richard B.; Healy, Claire; Holcatova, Ivana; et al. (Frontiers in Oncology, 2011)
Previous molecular epidemiological studies on head and neck cancer have examined various single nucleotide polymorphisms, but there are very few documented associations. In the International Head and Neck Cancer Epidemiology (INHANCE) consortium, we evaluated associations between SNPs in the metabolism, cell cycle, and DNA repair pathways and the risk of head and neck cancer. We analyzed individual-level pooled data from 14 European, North American, Central American and Asia case-control studies (5,915 head and neck cancer cases and 10,644 controls) participating in the INHANCE consortium. Unconditional logistic regression was used to estimate odds ratios (OR) and 95% confidence intervals (CI) for SNP effects, adjusting for age, sex, race, and country. We observed an association between head and neck cancer risk and MGMT Leu84Phe heterozygotes (OR=0.79, 95% CI=0.68-0.93), XRCC1 Arg194Trp rare homozygotes (OR=2.3, 95% CI=1.1-4.7), ADH1B Arg48His homozygotes Arg/Arg (OR=2.7, 95% CI=1.9-4.0), ADH1C Ile350Val homozygotes Ile/Ile (OR=1.2, 95% CI=1.1-1.4), and the GSTM1 null genotype (OR=1.1, 95% CI=1.0-1.2). Among these results, MGMT Leu84Phe, ADH1B Arg48His, ADH1C Ile350Arg, and the GSTM1 null genotype had fairly low false positive report probabilities (<20%). We observed associations between ADH1B Arg48His, ADH1C Ile350Arg, and GSTM1 null genotype and head and neck cancer risk. No functional study currently supports the observed association for MGMT Leu84Phe, and the association with XRCC1 Arg194Trp may be a chance finding.